The human capsular bag model of posterior capsule opacification - Wormstone, I. Michael (Eye (Lond), 2019)
Posterior capsule opacification (PCO) is the most common complication following cataract surgery and affects millions of patients. PCO is a consequence of surgical injury promoting a wound-healing response. Following surgery, residual lens epithelial cells grow on acellular regions of the lens capsule, including the central posterior capsule. These cells can undergo fibrotic changes, such that cell transdifferentiation to myofibroblasts, matrix deposition and matrix contraction can occur, which contribute to light scatter and the need for further corrective Nd:YAG laser capsulotomy in many patients. It is therefore of great importance to better understand how PCO develops and determine better approaches to manage the condition. To achieve this, experimental systems are required, and many are available to study PCO. While there may be a number of common features associated with PCO in different species, the mechanisms governing the condition can differ. Consequently, where possible, human systems should be employed. The human capsular bag model was established in a laboratory setting on donor eyes. A capsulorhexis is performed to create an opening in the anterior capsule followed by removal of the lens fibre mass. Residual fibre cells can be removed by irrigation/aspiration and if required, an intraocular lens can be implanted. The capsular bag is isolated from the eye and transferred to a dish for culture. The human capsular bag model has played an important role in understanding the biological processes driving PCO and enables evaluation of surgical approaches, IOLs and putative therapeutic agents to better manage PCO.